Radionuclide diagnosis of Meckel’s diverticulum: A case report - Dhima, Arben; Trushaj, Esilda; Blloshmi, Amarildo (European Scientific Journal, ESJ, 2024)
Introduction: Meckel’s diverticulum is a common congenital anomaly of the small intestine that results from the incomplete obliteration of the vitelline duct (omphalomesenteric duct). The most common symptom with which a patient presents to the emergency department is painless gastrointestinal bleeding. The most sensitive examination is the Meckel radionuclide scan using 99mTc-pertechnetate (known as the Meckel scan). In this case report, we present the case of an 18-year-old patient who presented with symptoms and was diagnosed with Meckel’s diverticulum through the Meckel scan. Methodology and Discussion: An 18-year-old male patient presented to the emergency department with hematochezia, abdominal pain for several days, nausea, and vomiting for the first time. After clinical assessment and objective examination, several tests were conducted, which all returned normal results. The clinical suspicion pointed towards Meckel’s diverticulum. The diagnosis was confirmed with a very simple examination: scintigraphy, a nuclear study performed by injecting technetium-99m, which is absorbed by the mucous-producing cells of the ectopic gastric mucosa. The patient underwent laparotomy, and the histopathological examination confirmed the diagnosis of Meckel’s diverticulum. Conclusion: Scintigraphy is the appropriate diagnostic modality in cases of unexplained gastrointestinal bleeding when there is clinical suspicion of Meckel’s diverticulum. It has very high specificity and sensitivity when performed according to protocol. Additionally, it is a low-cost examination with less radiation exposure compared to other imaging modalities.